A kinetic energy-based failure criterion for defining slope stability by PFEM strength reduction. (March 2023) - ZOU, Jiaqiang; YANG, Fangxin; YUAN, Weihai; LIU, Yihui; LIU, Aihua; ZHANG, Wei
Highlights: Two-dimensional explicit SPFEM considering kinetic energy is coupled with the strength reduction method, aiming at numerically defining the factor of safety (FOS) of the slope. The explicit algorithm introduced in this paper can avoid the influence of artificial error caused by using the number or accuracy of iterations. The occurrence time of peak kinetic energy is introduced to the slope failure analysis, which helps determine the safety factor, and the proposed criterion is verified by four different slopes. Compared with the current failure criteria, the proposed criterion considering the sudden change of occurrence time of peak kinetic energy can better identify the FOS of the slope, and will not increase the economic cost due to overestimation of FOS in engineering practice. Abstract: From the perspective of energy, the change of kinetic energy is rather obvious in the process of slope from steady state to failure. To numerically define the factor of safety (FOS) of the slope, the strength reduction method (SRM) is coupled with the two-dimensional explicit smoothed particle finite element method (eSPFEM), considered kinetic energy, to analyze slope stability. Through the failure analysis of slope, a new failure criterion based on the change of occurrence time of peak kinetic energy is proposed in this paper. Its applicability and accuracy are verified by two homogeneous slopes and two inhomogeneous slopes. The results show that the evolution of kinetic energy in the slope can intuitively and effectively reveal the sudden change of occurrence time of peak kinetic energy, leading to objectively determining the FOS of the slope. The proposed failure criterion regarding the characteristics of kinetic energy evolution could be further utilized in practical engineering to determine a more accurate factor of safety of the slope.